Expanding chemical biology of 2-oxoglutarate oxygenases. - Loenarz, C; Schofield, C (2008)
Beyond established roles in collagen biosynthesis, hypoxic signaling and fatty acid metabolism, recent reports have now revealed roles for human 2-oxoglutarate-dependent oxygenases in histone and nucleic acid demethylation and in signaling protein hydroxylation. The emerging role of these oxygenases in enabling a multiplicity of histone modifications has some analogy with their role in enabling structural diversity in secondary metabolism.